2022
DOI: 10.3846/btp.2022.16089
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Corporate Social Responsibility Perception on Job Performance: Does Corporate Reputation Matter?

Abstract: The objective of this study is to examine the relationship between corporate social responsibility (CSR) and job performance through the mediating role of job attitudes. In addition, the moderating role of organizational reputation is also considered. Based on stakeholder theories, signaling theory, social exchange theory, and social identity theory, a research model has been developed. Data has been collected from 636 employees working in SMEs in Vietnam to provide empirical evidence. Research results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Employees who are satisfied with their job will be inclined to be productive at work. Some studies indicated an expectation that employees with a higher level of satisfaction and experience leads to increased productivity (Akram et al, 2021;Giao et al, 2020b;Vuong et al, 2022a). Based on the social exchange theory of Blau (1964), employees who have gained satisfaction with their work may feel compelled to repay or reciprocate their organization.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Employees who are satisfied with their job will be inclined to be productive at work. Some studies indicated an expectation that employees with a higher level of satisfaction and experience leads to increased productivity (Akram et al, 2021;Giao et al, 2020b;Vuong et al, 2022a). Based on the social exchange theory of Blau (1964), employees who have gained satisfaction with their work may feel compelled to repay or reciprocate their organization.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…As one of the primary internal stakeholders of a bank, bank employees are directly involved in CSR activities and impact this success, therefore it is impossible to separate bank performance from bank employees. According to Vuong et al (2022), a company will get several advantages from a policy when it is committed to executing it for employees and addressing their demands. When employees feel happy by working at a bank, and the policies implemented meet the needs of employees, then employees will actively support the banking business so that mutual social exchange occurs, this is also specifically conveyed by Vuong (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The companies are more susceptible to reputation risks than others and are also more susceptible to negative stakeholder reactions (Mahmood & Bashir, 2020). Due to this, businesses frequently invest millions of dollars in CSR initiatives to enhance their reputation (Vuong et al, 2022). As a result, as stated by Li et al (2022), the concept of CSR has undergone significant changes and companies are now more vulnerable to social and environmental problems because they must maintain their good reputation in society.…”
Section: Introductionmentioning
confidence: 99%